THE EFFICACY OF TVS IN MEASURING CERVICAL PARAMETERS COMPARED TO THE BISHOP SCORE FOR PREDICTING LABOR INDUCTION OUTCOMES - Ghana Shahid; Shehnaz Sheeba; Adeela Anwar; Amina Akbar; Sadaf Afroze; Shakra Tabasam (Journal of Ayub Medical College Abbottabad, 2025)
Background: Labor induction requires accurate assessment of cervical readiness. The Bishop score is commonly used but is subjective and variable. Transvaginal ultrasonography (TVS) offers a more standardized approach. This study compares TVS and the Bishop score in predicting labor induction outcomes. Objective was to evaluate the efficacy of TVS in measuring cervical parameters compared to the Bishop score for predicting labor induction outcomes. Methods: This is a descriptive cross-sectional study conducted at Pakistan Air Force Hospital, Kamra and Pakistan Air Force Hospital, Islamabad from December 2023 till May 2024. Pregnant patients with cephalic singleton pregnancies were included. TVS and Bishop scores were recorded, and labor induction was initiated based on these scores. Data were analyzed using SPSS. Results: Of 100 participants, most were between 19 and 32 years old (mean age 21.23 years) and more than 39 weeks pregnant. Induction success rate was 81%. TVS scores above 4 correlated with successful inductions (93.2% success rate), while lower scores had a higher failure rate (93.24% sensitivity, 73.08% specificity). Conclusion: TVS is more accurate than the Bishop score in predicting labor induction outcomes. Its wider adoption could improve the success of labor induction and reduce complications.